FACTORS AFFECTING BEHAVIORAL INTENTION IN USING GO-PAY WITH THE MODIFIED UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY 2 MODEL (UTAUT2) - Nuriska, Alfia; Asakdiyah, Salamatun; Setyawan, Rai Raka (Muhammadiyah University Press, 2018)
The development of payment systems in Indonesia is in line with the global technological advancements and followed by new innovations, including the presence of e-money.As a subsidiary of PT Aplikasi Karya Anak Bangsa (Go-Jek), PT Dompet Anak Bangsa is the holder of the Go- Pay e-money license and included as one of 32 companies that have obtained license as e-money operators from Bank Indonesia. Despite the current high transaction growth of Go-Pay, it may not survive without any efforts to improve its service quality and expand the consumer preferences in using Go-Pay. Therefore, it is necessary to identify the factors that influence behavioral intention in using Go-Pay. This study aims to examine and determine the factors that influence behavioral intention in using Go-Pay with the modified Unified Theory of Acceptance and Use of Technology2 Model (UTAUT 2). This study uses a quantitative method with a questionnaire as the research instrument. The population of this study is Go-Pay users in the Special Region of Yogyakarta. The method of data analysis is SEM-PLS. The results showed that there were three factors that were significant in influencing people?s interest in using Go-Pay, namely: Habit, Facilitating Condition, and Price Value.